PROFIL KEMAMPUAN KONEKSI MATEMATIS SISWA SMA BERDASARKAN KEMAMPUAN MATEMATIKA: Profile of High School Students’ Mathematical Connection Ability Based on Mathematics Ability - Wunto, Cristovel; Ismaimuza, Dasa; Bennu, Sudarman (Jurnal Elektronik Pendidikan Matematika Tadulako, 2023)
The purpose of this study is to profile the mathematical connection ability of students who have high mathematical abilities in the sub-topic of trigonometric equations. The research design uses a qualitative approach. The study was conducted on students of St. Andreas Palu Catholic High School. The instruments used are written assignments and interview guidelines. The results of this study show that the connection ability  of students with high mathematical ability in solving equation problems in each category includes: 1) In  the modeling connection  category, students know the information in the problem completely and precisely this is characterized by  recognize the relationship between time and trigonometry so that students can use the formulas they know to determine when the right time is so that the ship can enter the port based on known equations. 2)  In the concept connection category, students understand the concept of trigonometric equations and trigonometric comparisons in solving trigonometric equation problems. However, the subject did not understand well the interrelationship of the concept of cosine trigonometric equations with the given question so that an incorrect final answer was obtained.  3) In the category of procedure connections, students relate concepts through appropriate procedures so that they can solve trigonometric equation problems.